2005
DOI: 10.4153/cjm-2005-045-7
|View full text |Cite
|
Sign up to set email alerts
|

The Square Sieve and the Lang–Trotter Conjecture

Abstract: Abstract. Let E be an elliptic curve defined over Q and without complex multiplication. Let K be a fixed imaginary quadratic field. We find nontrivial upper bounds for the number of ordinary primes p ≤ x for which Q(π p ) = K, where π p denotes the Frobenius endomorphism of E at p. More precisely, under a generalized Riemann hypothesis we show that this number is O E (x 17/18 log x), and unconditionally we show that this number is O E,K x(log log x) 13/12 (log x) 25/24 . We also prove that the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 6 publications
1
39
0
Order By: Relevance
“…These results improve upon earlier work of J.-P. Serre [19] and A. C. Cojocaru,É. Fouvry and M. R. Murty [6]. In the case of a = 0, better bounds are known: unconditionally, N. Elkies [10,11] has shown that, if E is without CM, there are infinitely primes p such that a p = 0 (for explicit lower bounds, see [11] and [13]).…”
Section: ) E(t) : Y 2 = X 3 + A(t)x + B(t) Over Q(t) Where A(t) B(supporting
confidence: 82%
“…These results improve upon earlier work of J.-P. Serre [19] and A. C. Cojocaru,É. Fouvry and M. R. Murty [6]. In the case of a = 0, better bounds are known: unconditionally, N. Elkies [10,11] has shown that, if E is without CM, there are infinitely primes p such that a p = 0 (for explicit lower bounds, see [11] and [13]).…”
Section: ) E(t) : Y 2 = X 3 + A(t)x + B(t) Over Q(t) Where A(t) B(supporting
confidence: 82%
“…In particular, using [CoFoMu,theorem 2·4] together with [CoFoMu,lemma 2·7] (see also [CoFoMu,lemma 2·8]), we obtain: LEMMA 3. For any elliptic curve E/Q without complex multiplication and any sufficiently large positive real number x, the estimate…”
Section: Preliminariesmentioning
confidence: 99%
“…We first recall some group theoretical results from [2]. We will then apply versions of the Chebotarev density theorem (under GRH or without) and obtain our results.…”
Section: Square-sieve Approachmentioning
confidence: 99%